Looming Greek tradegy in Hong Kong. - SZULC, Tad (1997)
Argues that Hong Kong may come to define US fundamental relationship with the People's Republic of China in a period when China is rapidly becoming the world's only other economic and military (and nuclear-armed) superpower.